2013
DOI: 10.1111/ecc.12112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation on the efficacy of CyberKnife for primary or metastatic retroperitoneal tumours

Abstract: The aim of the paper is to evaluate the efficacy of CyberKnife® for the treatment of primary or metastatic retroperitoneal tumours. Twenty-eight patients were treated. The prescription isodose line (median, 78%; range, 70-84%) covered the planning target volume at a total dose of 2000-6000 cGy (median, 4500 cGy) and a biologically effective dose of 3750-10,080 cGy (median, 7680 cGy) in 2-10 fractions (median, five fractions). The results showed that the complete response, partial response, stable disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The methodology used for CyberKnife SRT and treatment planning has been described in detail in our previous reports [ 21 - 23 ]. Briefly, patients were immobilized using a vacuum bag before CT simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used for CyberKnife SRT and treatment planning has been described in detail in our previous reports [ 21 - 23 ]. Briefly, patients were immobilized using a vacuum bag before CT simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used for CyberKnife SRT and treatment planning has been described in detail in our previous reports [21][22][23]. Briefly, patients were immobilized using a vacuum bag before CT simulation.…”
Section: Treatment Schedulementioning
confidence: 99%
“…There are few studies reported in the literature evaluating the response to guided radiotherapy with the CyberKnife system in patients with retroperitoneal tumors. A study by Zhuang H et al,23 reported a complete response and stability of the disease in 48% and 18% of the cases,…”
mentioning
confidence: 97%
“…23 . There are few studies reported in the literature evaluating the response to guided radiotherapy with the CyberKnife system in patients with retroperitoneal tumors.…”
mentioning
confidence: 99%